Obtención de un recubrimiento comestible a base de Mucílago de Nopal (opuntia spp.) y Aceite Esencial de Romero (rosmarinus officinalis) - Osorio Chuquitarco, Ninfa Mishel (2018)
The present work has as objective to obtain a coating edible based on mucilago of nopal (Opuntia spp.) and essential oil of rosemary (Rosmarinus offinalis), for industrial purposes, the use of coatings, comestible, polysaccharide, proteins, lipids, additives and active compounds has an important role in the industry food and have been shown to be effective in the conservation of fruits and vegetables by controlling gas transfer, microbial growth, while maintaining its characteristics such as, appearance, crispness, firmness, brightness, color, quality and commercial value. In addition, this research aims to give to know new alternatives for food preservation. The process of obtaining a coating edible based on mucilago of nopal (Opuntia spp.) and essential oil of rosemary (Rosmarinus offinalis), with two concentrations of mucilago, two of pectin and two of rosemary essential oil was performed in the following way: reception, cleaning of the nopal with a solution of 0.1 % of chlorinated water, peeled and chopped removing the skin of the prickly pear cactus, liquefied with the help of distilled water, cooking at a temperature of 80 ℃, keeping it at that temperature for 20 minutes, addition of two concentrations of pectin at 6% and 3 %, filtration through a fine sieve leaving it in the fridge for 2 hours at 5 ℃, was applied to the solution by immersion in the fruit (orange), leave it to dry for 15 minutes and store under refrigeration at a temperature of 5 ℃. It was subjected to physicochemical analysis during 4 weeks and was conducted in an experimental design DBCA with factorial arrangement An x B x C with 2 replicas to determine the best treatment was t7 (a2b2c) (97% of mucilago, and 3% of pectin and 1% of essential oil of rosemary). Described the physical and chemical characteristics of the best treatment: pH 3,2850, acidity, 0935, solids soluble 14.24 °Brix, weight loss 297.21 g.